Antioxidants positively regulate obesity dependent circRNAs - sperm quality - functional axis - Mele, Vincenza Grazia; Chioccarelli, Teresa; Finamore, Rosario; D’Agostino, Antonella; d’Agostino, Maria; Cimini, Donatella; Mattia, Monica; Porreca, Veronica; Giori, Andrea Maria; Fasano, Silvia; Cobellis, Gilda; Schiraldi, Chiara; et al. (Frontiers in Endocrinology, 2023)
Obesity is a pathophysiological condition, dependent on body fat accumulation, that progressively induces systemic oxidative stress/inflammation leading to a set of associated clinical manifestations, including male infertility. CircRNAs, covalently closed RNA molecules, are key regulators of sperm quality. Recently, we have characterized a complete profile of high-fat diet (HFD) spermatic circRNA cargo, predicting paternal circRNA dependent networks (ceRNETs), potentially involved in sperm oxidative stress and motility anomalies. In the current work, using HFD C57BL6/J male mice, orally treated with a mix of bioactive molecules (vitamin C; vitamin B12; vitamin E; selenium-Lmethionine; glutathione-GSH) for 4 weeks, a reversion of HFD phenotype was observed. In addition, the functional action of the proposed formulations on circRNA biogenesis was evaluated by assessing the endogenous spermatic FUSdependent backsplicing machinery and related circRNA cargo. After that, spermatic viability and motility were also analyzed. Paternal ceRNETs, potentially involved in oxidative stress regulation and sperm motility defects, were identified and used to suggest that the beneficial action of the food supplements here conveniently formulated on sperm motility was likely due to the recovery of circRNA profile. Such a hypothesis was, then, verified by an in vitro assay.